DESIGN OF THE PANCA MASK DOCUMENTARY FILM - I Wayan Dipa Mulyawan; I Nyoman Agus Suarya Putra; I Made Marthana Yusa (Yayasan Sinergi Widya Nusantara, 2025)
Purpose: This research was motivated by a problem the author discovered in Tulikup Village, Gianyar, namely the Panca Mask Dance, which is usually expressed through